1978
DOI: 10.1172/jci108988
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Renal Nerves and Prostaglandins in Control of Renal Hemodynamics and Plasma Renin Activity during Hypotensive Hemorrhage in the Dog

Abstract: A B S T R A C T The effects of hypotensive hemorrhage (HH) on renal hemodynamics and plasma renin activity (PRA) during prostaglandin (PG) synthesis inhibition were examined in three groups ofdogs. In each group of animals arterial blood pressure was lowered by a 30% decrement. In the first group of eight control animals, HH was not associated with a significant change in glomerular filtration rate (GFR, 42-36 ml/min, NS); renal blood flow (RBF) declined significantly, from 234 to 171 ml/min, P < 0.05. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
2

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(41 citation statements)
references
References 15 publications
3
36
0
2
Order By: Relevance
“…This finding is in agreement with other studies in which inhibition of prostaglandins reduced renal blood flow but had no effect on glomerular filtration rate (28); however, it contrasts with the observations that prostaglandin blockade significantly reduced the glomerular filtration rate in dogs with hypotensive hemorrhage (14,31) and in patients with Bartter's syndrome (42), with the nephrotic syndrome (43), and with cirrhosis with ascitis (16).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in agreement with other studies in which inhibition of prostaglandins reduced renal blood flow but had no effect on glomerular filtration rate (28); however, it contrasts with the observations that prostaglandin blockade significantly reduced the glomerular filtration rate in dogs with hypotensive hemorrhage (14,31) and in patients with Bartter's syndrome (42), with the nephrotic syndrome (43), and with cirrhosis with ascitis (16).…”
Section: Resultssupporting
confidence: 91%
“…Renal prostaglandin synthesis is increased in sodium depletion (30), hemorrhagic hypotension (31), renal artery constriction (31), and cirrhosis with ascitis (33). In all these conditions, administration of inhibitors of prostaglandin synthesis reduces renal blood flow (12,15,16,31). The mechanism(s) whereby the prostaglandins attenuate renal vasoconstrictor mechanisms remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…In a dog model of sepsis, the role of renal nerves was also demonstrated after prostacyclin inhibition (5), suggesting an interaction between prostaglandins and renal nerve stimulation. In that regard, it is known that both angiotensin and increased renal nerve activity stimulate vasodilating prostaglandins (PGI 2 and PGE 2 ) in the kidney (4). Previous studies have shown an upregulation of NO synthase activity with ␣-adrenergic activity (15,17).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 The systemic inflammatory state and the presence of interstitial nephritis act as important sources of prostaglandin and nitric oxide secretions, resulting in arterial hypotension, increased medullary blood flow, elevated interstitial pressure, and decreased renal tubular reabsorption of sodium, potassium, calcium, and magnesium in these patients. 33,34 Characteristics of primary thyroid insufficiency were observed in patients with high TSH, and low T 3 and free-T 4 plasmatic concentrations. Evidences of primary pituitary hypofunction and secondary hypothyroidism were observed in patients with low TSH and low free-T 4 plasma levels.…”
mentioning
confidence: 99%